Biomarkers of oxidative stress in women with pre-eclampsia. (April 2013) - Siddiqui, Imran A; Jaleel, Anila; Al'Kadri, Hanan MF; Akram, Sufyan; Tamimi, Waleed
Aim: The potential role of oxidative stress in the pathophysiology of pre-eclampsia has been reported in the literature. There are only a few studies that have investigated changes in malondialdehyde (MDA), vitamin E and total blood glutathione together in pre-eclampsia. Therefore, the aim of this study was to measure the levels of MDA, vitamin E and total glutathione as putative circulatory markers of oxidative stress for the early detection of pre-eclampsia.Patients & methods: In this case–control study, blood samples were collected from 40 pre-eclamptic and 80 normal pregnant females at the department of obstetrics and gynecology at King Abdulaziz Medical City (Riyadh, Saudi Arabia) between February 2009 and January 2010. Circulating markers of oxidative stress were evaluated, including MDA, total glutathione and vitamin E, by high-performance liquid chromatography.Results: Markers of oxidative stress including serum MDA, total glutathione and vitamin E were found to be significantly different in both groups.Conclusion: MDA, vitamin E and blood total glutathione are possible candidate markers to predict pre-eclampsia.